TikTok as an Interfaith Debate Space: Islamic and Christian Theological Dialogue from a Jidal Perspective - Jamaludin, Jamaludin; Yaqinah, Siti Nurul (Da’wa and Communication Faculty of the Sunan Ampel State Islamic University, Surabaya, Indonesia., 2024)
Abstract: This study aims to respond to the phenomenon of dialogue-based debate between Muslims and Christians through Tiktok social media today. Specifically, what are the patterns and abilities of Islamic debaters' communicators in arguing with Christian opponents when they live or stich videos. And what are the ethics of debate when they are live in the perspective of jidal communication. This problem is interesting to study, reminding that TikTok social media is not only an entertainment media looking for viral, but can be transformed as a religious da'wah media platform. Islam and Christianity have so far been the most viral in TikTok debates than other religions. So that with the current openness of TikTok media for da'wah activists to take advantage of this opportunity as a medium in conveying the values of religious truth, so that TikTok appears as an interfaith communication space. The data analysis process starts from data collection, data display and data verification. The results of this study indicate that TikTok as a religious meeting space for da'wah activists is very good to be used as a medium for da'wah, in conveying religious truths. The communication pattern built by Islamic debaters is non-complementary communication. And the ethics of Muslim debaters do not come out of Islamic values in debates, so that they are controlled and credible, so that many of these interfaith dialogues embrace Islam or convert to Islam based on the data obtained.